Mating Order Establishes Male Size Advantage in the Polygynandrous Millipede Centrobolus inscriptus Attems, 1928 - Mark Cooper (New Visions in Biological Science Vol. 9, 2022)
A forest species of millipede belonging to the Order Spirobolida found along the eastern coast of southern Africa were tested for size assortative mating. The objectives control for SSD in multiple mating to test for size advantages in mating. The male length was positively related to the duration of the first mating (rs=0.30, n=46, P=0.04) but negatively related to the duration of the second mating (rs=-0.35, n=46, P=0.02). Male length and copulation duration were different in first compared to second matings (z=3.13, n=46, 46, p<0.01); when female width (z=-0.59, n=46, 46, p=0.60) and SSD (z=-1.08, n=46, 46, p=0.28) were controlled. A mating order effect from positive to negative size advantage in mating was explained as a result of female choice based on male lengths.